GeoFun: Development of a 2D Game-Based Learning Mobile Application for Geometric Shapes to Primary School Students - WONG SHIAO XUAN,; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2025)
In Malaysia, geometry is a crucial mathematics topic in primary school, forming the foundation for 40% of the secondary school syllabus. In 2022, it was reported that Malaysian students' performance in the geometry domain consistently fell below the international average in the Trends in International Mathematics and Science Study (TIMSS). To address this, a 2D game-based learning mobile application named GeoFun is developed to strengthen Year 3 primary school students’ understanding of 2D and 3D geometry before progressing to more advanced levels of learning. The application is developed using the Multimedia Mobile Content Development (MMCD) methodology. Both functional and user acceptance testing are conducted, with GeoFun achieving an average System Usability Scale (SUS) score of 71.16%, indicating positive user acceptance. In conclusion, GeoFun proves to be a suitable supplementary tool for enhancing students’ foundational geometry knowledge through an engaging and interactive learning experience.